Upregulation of exosomal integrin β4 causes osteosarcoma cell proliferation via the PI3K-Akt-mTOR signaling pathway - Wang, Qianrong; Shi, Zhenghua; Zhang, Hongmei; Liu, Wenchao; Yu, Zhicao; Zhang, Qiong (Translational Cancer Research, 2018)
Background: Osteosarcoma is the most common primary bone malignant tumor in adolescents and young adults. Although the molecular pathogenesis of osteosarcoma is well studied, the role of integrin β4 in the progression of osteosarcoma is still largely unknown. Methods: Using blood samples obtained from 46 patients and 38 healthy donors as well as human osteosarcoma cell lines MG-63 and U2-OS, we investigated the roles of integrin β4 in the proliferation of osteosarcoma cells. Results: Integrin β4 was commonly overexpressed in the serum and exosomes of patients with osteosarcoma, and this phenomenon significantly correlated with advanced tumor stage. Furthermore, in vitro experiments indicated that a knockdown of integrin β4 could notably suppress proliferation of both MG-63 and U2-OS cells, and upregulate the p16, p21, and p27 proteins in osteosarcoma cells. By means of PI3K inhibitor LY294002, we found that the PI3K–Akt–mTOR signaling pathway may be involved in the effect of integrin β4 on the proliferation of osteosarcoma cells. Conclusions: This study for the first time demonstrates that β4 integrin is highly expressed in osteosarcoma cell lines and in high-grade osteosarcoma tumors, and the larger amount of β4 integrin promotes proliferation of osteosarcoma cells (i.e., cancer progression) possibly via the PI3K–Akt–mTOR signaling pathway.